Characterization of chickpea gene pools for nutrient concentrations under agro-climatic conditions of North-Western Himalayas. Issue 5 (10th October 2019) - Fayaz, Humara; Rather, Irshad Ahmad; Wani, Aijaz A.; Tyagi, Sandhya; Pandey, Renu; Mir, Reyazul Rouf
Abstract: Chickpea is one of the most important nutritious grain legume crops in the world. There is limited information available on micro- and macro-nutrients in chickpea. Therefore, an effort was made to evaluate a set of 40 chickpea genotypes belonging to all the gene pools including cultivated ( Cicer arietinum ) as well as wild, Cicer reticulatum from the primary gene pool, Cicer echinospermum from the secondary gene pool and Cicer microphyllum from the tertiary gene pools. Concentration in the seed of the micro- (Zn, Fe, Cu and Mn) and macro-nutrients (Ca, Mg and K) was studied. Substantial variation was observed among different gene pools for the concentration of all the nutrients. The cultivated chickpea exhibited higher seed Cu, Mn, Mg and Ca than wilds indicating positive domestication effect, whereas wild crop relatives were found to have higher levels than cultivated chickpeas for seed Zn, Fe and K concentrations. While comparing desi -type chickpeas with Kabulis, it was revealed that desi types possessed more Zn, Cu, Ca and Mg than Kabulis but reverse was true for seed Fe, Mn and K. Among different desi types ( desi brown, desi green and desi black), desi brown types were generally associated with higher mineral nutrient levels. The present study led to the identification of most promising genotypes for different seed micro- and macro-nutrients. These promising lines may serve as genetic resources useful in gene discovery programmes and for alleviating malnutrition or hidden hunger in the developing world.